Penerapan Presentation Activity Dalam Melatih Kemampuan Literasi Sains Siswa Kelas Xi Pada Topik Jaringan Tumbuhan - Allan, Ivana Ananda Pradita; Bermuli, Jessica Elfani (Universitas Muhammadiyah Prof. Dr. Hamka, 2025)
Background: In general education, literacy skills are a must for students. The capacity to recognize problems, reach conclusions, and use scientific information in daily situations is known as scientific literacy. Students who are scientifically literate in Christian education will have a deeper understanding of God and His creation as they recognize the order found in all living things. The goal of this final project is to clarify how presentation activities might be used to help students in class XI develop their scientific literacy. Methods: A descriptive qualitative approach to analysis is applied. Finally, incorporate presenting exercises into the classroom and prepare extra notes for the presentation. Answering, explaining, identifying, and analyzing questions are examples of scientific literacy indicators demonstrating how well the presentation activity went, searching for relevant literature, and locating it. Results: All students looked confused and could not answer the teacher's questions. Six out of 10 students could not explain what was known about plant tissue. Eight out of 10 students could not analyze and identify the location characteristics. Conclusions: Implementing presentation activities in the classroom has proven to train students' scientific literacy skills. The stages of presentation activities include determining the presentation topic, knowing the audience's needs, determining the purpose of the presentation, determining the core information to be conveyed, creating the presentation content, determining the opening and closing of the presentation, and making special notes for the presentation, are considered to be able to train the scientific literacy skills of grade XI students.